Comparação entre a variação da pressão de pulso e o índice de variabilidade pletismográfica como índices dinâmicos de pré-carga em cães anestesiados com isoflurano submetidos à hemorragia hipotensiva por reposição volêmica - Klein, Adriana Vieira [UNESP] (2015)
Klein, A. V. Comparison of changes in pulse pressure variation and in plethysmographic variability index induced by hypotensive hemorrhage followed by volume replacement in isoflurane-anesthetized dogs. 72 p. Dissertation (MSc) - School of Medicine, São Paulo State University, Botucatu, 2015. The pulse pressure variation (PPV) and the pletysmographic variability index (IVP) are parameters that may identify individuals in which an increase in preload achieved by volume expansion will result in an increase in stroke index (SI) and in cardiac index (CI). This study aimed to compare the PPV and the PVI as dynamic preload indexes in isoflurane-anesthetized dogs undergoing hypotensive hemorrhage followed by volume replacement (VR) with autologous blood. In a prospective study, seven adult dogs weighing 25,1 ± 3,4 kg (mean ± standard deviation) were anesthetized with isoflurane under volume controlled ventilation (tidal volume: 12 mL/kg) and atracurium neuromuscular blockade. End-tidal isoflurane concentrations, adjusted to maintain mean arterial pressure (MAP) at 65 mmHg (± 5 mmHg range) before hemorrhage, were maintained constant throughout the study. Cardiac output was measured by the pulmonary thermodilution technique, while PPV and PVI were derived from invasive blood pressure from a pulse oxymeter placed in the tongue, respectively. Variables were recorded before hemorrhage (baseline), after withdrawing blood until MAP was decreased to 45 mmHg (± 5 mmHg range), and after VR with autologous blood over 30 minutes. Hemorrhage significantly (P < 0.05) decreased SI and CI from baseline; while VR normalized these variables. The PPV and PVI significantly increased from baseline after hemorrhage. Changes from baseline induced by hemorrhage were significantly higher for PPV (11 ± 5%) than for PVI (5 ± 5%). After VR, PPV returned to baseline while PVI decreased significantly from baseline. Changes from hemorrhage induced by VR were ...